Service quality perceptions and customer satisfaction in life insurance companies in Labuan / Muhammad Ashraf Zulkifli - Zulkifli, Muhammad Ashraf (2014)
This paper aims to evaluate the service quality perceptionsand customer satisfaction of Life Insurance Companies in the Federal Territory of Labuan through customer’s assessment. A total of 120 respondents who had life insurance policies wereparticipated in answering the questionnaires, in order to gather information related to their perception of service quality in the life insurance company they committed with. Descriptive analysis such as percentage and table presentations was used to analyse the collected data. The study revealed that among the five service quality dimensions (Assurance, Reliability, Tangible, Empathy, Responsiveness), privacy of customer’s information of assurance dimension is the most important factor considered by the customers. Through the regression analysis done, reliability dimension of service quality found to be the most significant factor that influences customer satisfaction.